BRCA1, BRCA2 mutations and the association with the clinicopathological characteristics of women with early-onset breast cancer - Ghazali, Mohamad Bazli (2014)
Introduction: BRCA1 and BRCA2 mutations have been associated with early-onset breast cancers and adverse clinico-pathological features. To date, there is paucity of studies in Malaysia investigating the relationship between types of BRCA1/2 mutations and clinicopathological characteristics of breast cancers. This study therefore aims to ascertain whether there are differences between different types of BRCA1/2 mutations in terms of clinico-pathological attributes of breast cancers amongst females with early-onset breast cancers in Malaysia. Methodology: Seventy females aged 40 or less with confirmed breast cancer diagnosis that underwent follow-ups at Seberang Jaya Hospital, Penang were recruited into this study. Clinical (age, ethnicity, stage, neo adjuvant therapy, family history of ovarian and breast cancers) and pathological (ER, PR, Her2 status, triple negativity, tumour grades and stages) characteristics of the breast cancers were obtained by retrospectively reviewing the medical records. Three mls of blood was taken from each subject and subjected to DNA extraction. These were then screened for germline mutations of BRCA1 gene (exons 11, 13 and 16) for BRCA2 gene (exons 10 and 11) using allele-specific PCR. Results: The prevalence of BRCA2-only and combined BRCA1 and BRCA1 mutations were 28.6% (95% CI: 18%, 39.2%) and 71.4% (95% CI: 60.8%, 82.0 %), respectively. No wild-type BRCA1 or BRCA2 and BRCA1-only mutations were observed in this study cohort. No significant associations were found between types of BRCA mutations (BRCA2-only mutations vs combined BRCA1 and BRCA2 mutations) and clinico-pathological characteristics of breast tumour. However, three BRCA1 mutations (3232A>G (rs16941, exon 11), 3667A>G (rs16942, exon 11) and 4427T<C (rs1060915, exon 13) were significantly associated with a more advanced tumour size group (p values = 0.032, 0.049 and 0.043, respectively). Besides, 3232A>G (rs16941, exon 11) mutation was also significantly associated with higher risk of HER2-negative (OR 7.50 (95% CI: 1.439, 39.089), p value = 0.017) and triple negative breast carcinoma (OR 4.375 (95% CI: 1.193, 16.038), p value =0.042). No significant associations were found between BRCA2 genotypes and clinico-pathological features of breast carcinoma. Conclusion: Combined BRCA1 and BRCA2 mutations are the most prevalent types of BRCA mutations amongst females with early onset breast cancers, followed by BRCA2-only mutations. Three BRCA1 germline mutations were found to be significantly predictive of a more advanced tumour size group whilst only one BRCA1 mutation was significantly associated with HER2-negative and triple negative breast tumours. Nevertheless, further studies are warranted to address the unresolved issues encountered by this study.